Oxidative Stress and Antioxidants in Uterine Fibroids: Pathophysiology and Clinical Implications - Abdelrahman AlAshqar; Bethlehem Lulseged; Akailah Mason-Otey; Jinxiao Liang; Umme Aoufa Mafruha Begum; Sadia Afrin; Mostafa A. Borahay (MDPI AG, 2023)
In the last few decades, our understanding of the complex pathobiology of uterine fibroid development has grown. While previously believed to be a purely neoplastic entity, we now understand that uterine fibroids possess different and equally important aspects of their genesis. An increasing body of evidence suggests that oxidative stress, the imbalance between pro- and antioxidants, is an important factor in fibroid development. Oxidative stress is controlled by multiple, interconnecting cascades, including angiogenesis, hypoxia, and dietary factors. Oxidative stress in turn influences fibroid development through genetic, epigenetic, and profibrotic mechanisms. This unique aspect of fibroid pathobiology has introduced several clinical implications, both diagnostic and therapeutic, that can aid us in managing these debilitating tumors by using biomarkers as well as dietary and pharmaceutical antioxidants for diagnosis and treatment. This review strives to summarize and add to the current evidence revealing the relationship between oxidative stress and uterine fibroids by elucidating the proposed mechanisms and clinical implications.